The Ways to Explore and Include the Potential of the Armenian Diaspora - Karapetyan, Ruben (History and Culture, 2023)
The article discusses ways to clarify the purposes of the study of the Armenian Diaspora, as well as methodological approaches to identifying and studying the potential of the Diaspora.By improving their professional skills in the international arena and gaining significant economic, social and political weight, Diaspora Armenians have the potential to establish international structures on a national basis that can become a platform for political, economic, social and cultural cooperation. Collecting and analyzing information about the situation in each part of the diaspora will make it possible to identify and assess opportunities and prospects for developing and implementing community and national programs.
Keywords: potential; integration; diaspora; dispersed groups; discrete groups; community; ethno-social resources; resource analysis